2020
DOI: 10.1186/s12903-020-01086-7
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal inflamed surface area in patients on haemodialysis and peritoneal dialysis: a Croatian cross-sectional study

Abstract: Background: The decision to initiate dialysis treatment via haemodialysis (HD) or peritoneal dialysis (PD) often involves the consideration of complex factors and remains a matter of debate. The purpose of this study was to quantify the inflammatory burden that periodontitis causes in dialysis patients and to examine whether patients on PD and HD differ in terms of the periodontal inflamed surface area (PISA), which can be helpful for selecting the most appropriate dialysis modality. Methods: A cross-sectional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…After removing duplicates of references that were selected from more than one database, 1293 references remained. In total, 43 articles were included for data extraction (Table 1): 1 RCT, 36 cross‐sectional studies, three case–control studies, two cohort studies and one longitudinal study (Al‐Wahadni & Al‐Omari, 2003; Bayraktar et al, 2008; Bots et al, 2004; Bots et al, 2006; Bots et al, 2007; Bruzda‐Zwiech, Szczepańska, & Zwiech, 2014; Bruzda‐Zwiech, Szczepańska, & Zwiech, 2018; Chuang, Sung, Kuo, Huang, & Lee, 2005; de la Rosa García, Mondragón Padilla, Aranda Romo, & Bustamante Ramírez, 2006; Dirschnabel et al, 2011; Eltas, Tozoğlu, Keleş, & Canakci, 2012; Gautam et al, 2014; Gavaldá et al, 1999; Honarmand, Farhad‐Mollashahi, Nakhaee, & Sargolzaie, 2017; Jain et al, 2014; Jung & Chang, 2020; Kaushik et al, 2013; Kho, Lee, Chung, & Kim, 1999; Križan Smojver, Altabas, Knotek, Bašić Jukić, & Aurer, 2020; López‐Pintor, López‐Pintor, Casañas, de Arriba, & Hernández, 2017; Malekmakan, Haghpanah, Pakfetrat, Ebrahimic, & Hasanlic, 2011; Marakoglu, Gursoy, Demirer, & Sezer, 2003; Marinoski, Bokor‐Bratic, Mitic, & Cankovic, 2019; Menezes et al, 2019; Misaki, Fukunaga, & Nakano, 2020; Murali, Narasimhan, Periasamy, & Harikrishnan, 2012; Naruishi et al, 2016; Oliveira et al, 2020; Pallos et al, 2020; Palmer et al, 2016; Parente et al, 2018; Perozini et al, 2017; Schmalz et al, 2016; Schmalz et al, 2017; Schütz et al, 2020; Sekiguchi, Pannuti, Silva, Medina‐Pestana, & Romito, 2012; Sobrado Marinho et al, 2007; Swapna et al, 2013; Tadakamadla, Kumar, & Mamatha, 2014; Torres et al, 2010; Yue et al, 2018; Zhao et al, 2014). The flow chart of the search and selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates of references that were selected from more than one database, 1293 references remained. In total, 43 articles were included for data extraction (Table 1): 1 RCT, 36 cross‐sectional studies, three case–control studies, two cohort studies and one longitudinal study (Al‐Wahadni & Al‐Omari, 2003; Bayraktar et al, 2008; Bots et al, 2004; Bots et al, 2006; Bots et al, 2007; Bruzda‐Zwiech, Szczepańska, & Zwiech, 2014; Bruzda‐Zwiech, Szczepańska, & Zwiech, 2018; Chuang, Sung, Kuo, Huang, & Lee, 2005; de la Rosa García, Mondragón Padilla, Aranda Romo, & Bustamante Ramírez, 2006; Dirschnabel et al, 2011; Eltas, Tozoğlu, Keleş, & Canakci, 2012; Gautam et al, 2014; Gavaldá et al, 1999; Honarmand, Farhad‐Mollashahi, Nakhaee, & Sargolzaie, 2017; Jain et al, 2014; Jung & Chang, 2020; Kaushik et al, 2013; Kho, Lee, Chung, & Kim, 1999; Križan Smojver, Altabas, Knotek, Bašić Jukić, & Aurer, 2020; López‐Pintor, López‐Pintor, Casañas, de Arriba, & Hernández, 2017; Malekmakan, Haghpanah, Pakfetrat, Ebrahimic, & Hasanlic, 2011; Marakoglu, Gursoy, Demirer, & Sezer, 2003; Marinoski, Bokor‐Bratic, Mitic, & Cankovic, 2019; Menezes et al, 2019; Misaki, Fukunaga, & Nakano, 2020; Murali, Narasimhan, Periasamy, & Harikrishnan, 2012; Naruishi et al, 2016; Oliveira et al, 2020; Pallos et al, 2020; Palmer et al, 2016; Parente et al, 2018; Perozini et al, 2017; Schmalz et al, 2016; Schmalz et al, 2017; Schütz et al, 2020; Sekiguchi, Pannuti, Silva, Medina‐Pestana, & Romito, 2012; Sobrado Marinho et al, 2007; Swapna et al, 2013; Tadakamadla, Kumar, & Mamatha, 2014; Torres et al, 2010; Yue et al, 2018; Zhao et al, 2014). The flow chart of the search and selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Schütz et al described that 59.4% of ESRD patients was diagnosed with severe periodontitis (Schütz et al, 2020). One study reported the total surface area of inflamed periodontal tissue (PISA score) per patient (Križan Smojver et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have used PISA for evaluation of periodontal conditions. Since PISA reflects the inflammation status of periodontal tissue, these studies focused on the correlation of PISA and systemic diseases [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], or the correlation of PISA with novel disease markers [41][42][43][44][45][46][47][48]. In the present study, IRT analysis was used to set a cut-off point for the number of bleeding sites and the maximum values of PD in a single tooth.…”
Section: Discussionmentioning
confidence: 99%
“…These periodontal parameters were measured following previously published studies for periodontal assessment and diagnosis 45 – 47 . Based on those results, PISA scores were calculated using an online calculator available at www.parsprototo.info as previously described 48 .…”
Section: Methodsmentioning
confidence: 99%